+0  
 
0
44
1
avatar

Compute 

\(1 + \frac{1}{3} + \frac{2}{3} + \frac{2}{9} + \frac{4}{9} + \frac{4}{27} + \frac{8}{27} + \frac{8}{81} + \dotsb\)

 

compute \(1 - 2 + 3 - 4 + \dots + 2005 - 2006 + 2007\)

Guest Feb 26, 2017
edited by Guest  Feb 26, 2017
Sort: 

1+0 Answers

 #1
avatar+18356 
0

compute 

1 - 2 + 3 - 4 + \(\dots \)+ 2005 - 2006 + 2007 = ?

 

Geometric series:

\(\begin{array}{|rcll|} \hline 1+x+x^2+x^3+x^4+x^5+\dots + x^n &=& \dfrac{1-x^{n+1}}{1-x} \qquad -1 < x < 1 \\ \hline \end{array} \)

 

Derivative:

\(\begin{array}{|rcll|} \hline 1+2x+3x^2+4x^3+5x^4+6x^5+\dots + nx^{n-1} &=& \dfrac{1-x^n[~n(1-x)+1~]}{(1-x)^2} \\ \hline \end{array} \)

 

x \(\rightarrow \) -x

\(\begin{array}{|rcll|} \hline 1-2x+3x^2-4x^3+5x^4-6x^5+-\dots + n(-x)^{n-1} &=& \dfrac{1-(-x)^n[~n(1+x)+1~]}{(1+x)^2} \\ \hline \end{array} \)

 

x = 1:

\(\begin{array}{|rcll|} \hline 1-2+3-4+5-6+-\dots + n(-1)^{n-1} &=& \dfrac{1-(-1)^n[~2n+1~]}{4} \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline && \sum \limits_{n=1}^{2007}n (-1)^{n - 1} = 1 - 2 + 3 - 4 + \dots + 2005 - 2006 + 2007 \\\\ &=& \dfrac{1-(-1)^{2007}[~2\cdot2007+1~]}{4} \\\\ &=& \dfrac{1+4015}{4} \\\\ &=& \dfrac{4016}{4} \\\\ &\mathbf{=}& \mathbf{1004} \\ \hline \end{array} \)

 

 

laugh

heureka  Feb 27, 2017

11 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details